1982
DOI: 10.1227/00006123-198203000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Vasospasm by Early Operation with Removal of Subarachnoid Blood

Abstract: Sixty-four patients who were operated on within 4 days after acute subarachnoid hemorrhage are included in this study. All patients underwent preoperative computed tomographic (CT) scanning, and the amount and distribution of subarachnoid blood clot were noted. Operation was carried out by the frontobasal lateral approach, and the subarachnoid clot was removed by microsurgical suction-irrigation after clipping of the aneurysm. Immediate postoperative CT scanning was performed to evaluate the completeness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Expert opinions differ largely. Some authors describe that during neurosurgical clipping, the blood clot (and thereby spasmogenic agents) can be removed from the subarachnoid space, which would diminish the risk of symptomatic vasospasm and DCI [6, 7]. Others believe that manipulation of the brain and abluminal vessel walls during surgery increases the risk of vasospasm and DCI [8], when compared to the risk of DCI after coiling.…”
Section: Introductionmentioning
confidence: 99%
“…Expert opinions differ largely. Some authors describe that during neurosurgical clipping, the blood clot (and thereby spasmogenic agents) can be removed from the subarachnoid space, which would diminish the risk of symptomatic vasospasm and DCI [6, 7]. Others believe that manipulation of the brain and abluminal vessel walls during surgery increases the risk of vasospasm and DCI [8], when compared to the risk of DCI after coiling.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of treatment used for the aneurysm on the incidence of cerebral vasospasm and consequent delayed ischemic neurologic deficit is largely unknown, previous reports have suggested that vasospasm might be prevented by clot removal within 48–72 h of SAH [9, 10, 11, 12, 13]. Furthermore, the irrigation of the cisterns by the same way has been reported to produce some success in preventing cerebral vasospasm [11, 12, 13, 14, 15, 16]. Whereas partial or complete removal of subarachnoid blood is possible during early aneurysm surgery, this procedure cannot be used in aneurysms treated with endovascular techniques [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are studies where the results have failed to prove the efficacy of clot removal,some authors have demonstrated its role in vasospasm reduction, while others have suggested that its benefits could likely be overlapped by secondary cerebral lesions caused by brain retraction or a higher incidence of vasospasm triggered by vessel manipulation during surgery …”
Section: Discussionmentioning
confidence: 99%